Phase-locked polarization by photospheric reflection in the semidetached eclipsing binary μ1 Sco. Issue 2 (13th July 2020) - Cotton, Daniel V; Bailey, Jeremy; Kedziora-Chudczer, Lucyna; De Horta, Ain
ABSTRACT: We report the detection of phase-locked polarization in the bright ( mV  = 2.98−3.24) semidetached eclipsing binary μ 1 Sco (HD 151890). The phenomenon was observed in multiple photometric bands using two different HIPPI-class (HIgh Precision Polarimetric Instrument) polarimeters with telescopes ranging in size from 35 cm to 3.9 m. The peak-to-trough amplitude of the polarization is wavelength dependent and large, ∼700 ppm in green light, and is easily seen with even the smallest telescope. We fit the polarization phase curve with a synspec /vlidort polarized radiative transfer model and a Wilson–Devinney geometric formalism, which we describe in detail. Light from each star reflected by the photosphere of the other, together with a much smaller contribution from tidal distortion and eclipse effects, wholly accounts for the polarization amplitude. In the past, polarization in semidetached binaries has been attributed mostly to scattering from extra-stellar gas. Our new interpretation facilitates determining masses of such stars in non-eclipsing systems.